Optimalisasi Digital Marketing untuk Pemasaran Kuda Lumping sekaligus Pelestarian Seni Budaya Desa Karangrejo Kabupaten Kediri - Dema Yulianto; Encil Puspitoningrum; Moch Muarifin; Achmad Fathoni Firmansyah; Dimas Sandi Pradana (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
This article discusses the optimization of digital marketing as a means for marketing and preserving the art of kuda lumping in Karangrejo Village, Kediri District. The art of kuda lumping, which is a combination of dance, music, and spiritual elements, faces challenges in maintaining its existence in the midst of modernization. Limited digital knowledge and low exposure among craftsmen have caused this art to be marginalized. Through a community service program, intensive training and mentoring on digital marketing strategies were conducted. The results of this program showed a significant increase in digital knowledge and skills among artisans and youth organizations. In addition, the program succeeded in strengthening awareness of the importance of cultural preservation through digital media. The program also proved that with the support of technology, traditional arts can remain relevant and competitive in the modern market. This article emphasizes the importance of implementing digital marketing to support a culture-based creative economy. This model is expected to be adapted by other communities in Indonesia in an effort to preserve and promote traditional arts in the digital era.